Ambient mass spectroscopy techniques in food and environment - Nollet, Leo M. L., 1948-; Munjanja, Basil K. (Boca Raton : Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T&F Informa, plc, 2019)
Ambient mass spectrometry--that is the use of mass spec but in the atmospheric environment--has been widely employed in food and environmental analysis. Ambient Mass Spectroscopy Techniques in Food and the Environment presents the theoretical underpinnings of mass spectrometry, and the benefits and pitfalls of ambient mass spectrometry, as well as the latest developments of the technique, in the analysis of food and environmental parameters. It describes methods that enable the detection of surface materials like waxes, alkaloids, flavors, or pesticides by plainly exposing the corresponding items to the ionization region of the interface, without harm to samples. Features: Explains the theoretical aspects of ambient mass spectrometry Describes how to use ambient MS techniques for food safety, authenticity, and traceability screening Lists the benefits of ambient MS in analysis of food and environmental parameters Covers recent developments of ambient MS in analysis of food and environmental parameters The specialized work provides insight to professionals practicing in food and the environment, including food scientists, food engineers, food biotechnologists, chemical engineers, and those working in research labs, universities, and government regulatory agencies.
OCLC-licensed vendor bibliographic record.
Keywords: Food -- Analysis; Spectrum analysis; TECHNOLOGY & ENGINEERING / Food Science; SCIENCE / Spectroscopy & Spectrum Analysis; TECHNOLOGY / Food Science